Scanning Electron Microscopic and Electrophoretic Studies on Clotting Factor Adsorbents - Deacon, S. L. M; Howell, R. M (Thrombosis and Haemostasis, 1976)
Physical studies carried out on a range of protein and clotting factor adsorbents revealed marked morphological and charge differences. Their appearance in the scanning electron microscope could be used to classify the insoluble precipitates, calcium phosphate, barium sulphate and citrate, as either amorphorous or crystalline.Surface charge is difficult to define but the present studies on the sparingly-soluble salts, based on calcium and barium, have revealed that they can be subdivided on the basis of the presence or absence of a charge reversal point in the pH-mobility curve. The anion component appeared to determine this characteristic; it was noted that phosphate and citrate ions had a marked effect and gave a biased negative potential at all pH values. We concluded that where a divalent cation is cohabiting with a trivalent anion, the greater potential-determining ability of the latter will dominate the overall charge at the surface of a particle, even below pH7 and the absence of a positive potential gives a monophasic pH-mobility curve.Differences in both the physical appearance and electrophoretic mobility of the adsorbents studied reflect the wide variation in their chemical composition, especially among the various forms of calcium phosphate which, unlike barium sulphate, can include substituted ions such as hydroxyl, in their crystal lattice. The definition of these characteristics allows their behaviour towards clotting factors to be more easily predicted.